A importância dos jogos pedagógicos na educação infantil - ARAÚJO, Fernanda da Silva (2023)
The present work aims to rescue the memories of my school journey and the importance of this whole process even today as a teacher and student in the Pedagogy course at PARFOR (National Teachers Plan). In this regard, I consider Education essential in the formation of a child, adolescent and adult. It is the primordial key to expand our intellectual, moral and social formation. Through a past rescue I was able to remember and remember all the path taken from my school life to the beginning of my life as a teacher and academic and I believe that there were several overcomings, there are no words to describe the beginning of my trajectory as a teacher , today I consider myself an educator. And this whole path transcribed allowed me to learn and I am learning every day, so that I can develop a guided work, seeking to exercise my role as an educator, the best possible, within my possibilities, to achieve a transforming education for our students.